Normative data for trachea and main bronchi dimensions on computed tomography in children and adolescents (Annals of Medical Research, 2021)
Aim: To determine the reference values for trachea and main bronchi dimensions in children and adolescents using CT and to evaluate correlations with age and sex.Material and Methods: This retrospective study evaluated 150 cases (75 males, 75 females) with the median age of 9 (6-14) years. Cases were divided into three groups according to age of 4-7 years (n=50, preschool), 8-12 years (n=50, school), and 13-17 years (n=50, adolescent). The dimensions of trachea segments (proximal, middle, distal parts), and right and left bronchi were measured on coronal CT images. Comparisons were made between age groups and sex in terms of these variables.Results: The proximal, middle and distal sections of the trachea had median dimensions of 0.91 (0.79-1.08)cm, 1.08 (0.96-1.22)cm and 1.17 (1.06-1.32)cm, respectively. The order from statistically largest to smallest was distal, middle and proximal levels (p0.001). The dimension of the right main bronchus was significantly larger than the left one (p0.001) (median dimension for right 1.11 [0.96-1.30]cm, for left 1.04 [0.91-1.22]cm). There were no significant differences between the genders for main bronchi and trachea proximal and middle sections in terms of size. The trachea distal dimension was significantly larger in males compared to females (p=0.036). There were significant differences for all airways dimensions between the age groups (p0.001) (from largest to smallest; adolescents, children, preschoolers).Conclusion: Quantitative normative data were determined for the central airways of children and adolescents using coronal CT. These values may be used for diagnosis and management of medical procedures in routine practice.
Keywords: Adolescents; bronchus; children; computed tomography; trachea, reference values